2021
DOI: 10.22500/8202031163
|View full text |Cite
|
Sign up to set email alerts
|

The Moyooka: Socio-Cultural Value of Halmahera Woman in Rural Household Livelihood

Abstract: This article aims to describe the socio-cultural value of Halmahera woman, known as Moyooka, in rural household livelihood. This research conducted in North Halmahera District, North Maluku Province of Indonesia. Qualitative method and case study approaches were used to examine the role of Halmahera woman in sustaining rural household livelihood through the case of Boeng and Huboto tribes, located in Tunuo and Pitu Village. In-depth interviews, observation, and document studies were used during data collection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Several previous studies using a sustainable livelihood framework have shown that mobility and the capability of access to forms of capital determine the sustainability of local people's livelihoods. Still, not all contexts show social capital as initial capital to access other forms of capital (Singgalen, 2020b(Singgalen, , 2020a(Singgalen, , 2020c(Singgalen, , 2022Singgalen et al, 2017Singgalen et al, , 2019c. Le & Vo (2021) show that the context of vulnerability also affects people's access capabilities to this form of capital to maintain sustainable livelihoods.…”
Section: Tourism Development and Livelihood Sustainabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies using a sustainable livelihood framework have shown that mobility and the capability of access to forms of capital determine the sustainability of local people's livelihoods. Still, not all contexts show social capital as initial capital to access other forms of capital (Singgalen, 2020b(Singgalen, , 2020a(Singgalen, , 2020c(Singgalen, , 2022Singgalen et al, 2017Singgalen et al, , 2019c. Le & Vo (2021) show that the context of vulnerability also affects people's access capabilities to this form of capital to maintain sustainable livelihoods.…”
Section: Tourism Development and Livelihood Sustainabilitymentioning
confidence: 99%
“…However, implementing community-based tourism in Indonesia is challenging, so it needs to be studied comprehensively and contextually. This research is a development of previous research on community-based tourism approaches in Indonesia, especially in North Maluku Province (Morotai et al, 2013;Singgalen et al, 2019bSinggalen et al, , 2019aSinggalen et al, , 2021. This study aims to outline the dynamics of implementing the concept of community-based tourism in Pringsewu Regency, Lampung Province, Indonesia, which shows explicitly the efforts of the tourism awareness group and other stakeholders in developing tourism products and services in tourist destinations.…”
Section: Introductionmentioning
confidence: 97%
“…Strategies to maintain business continuity in the face of challenges and threats caused by the Covid-19 pandemic need to be analyzed based on the perspective of capital, the context of vulnerability, and policy and institutional interventions. Previous studies have shown that the use of capital in the dynamics of entrepreneurship depends on the mobility of access to the capital (Singgalen, Kusumawicitra, et al, 2021), policy and institutional interventions to increase the capability of access to the capital (Singgalen, 2020a(Singgalen, , 2020b, to the context of vulnerability (Singgalen, 2021). In addition, shows that human capital is essential in optimizing small-scale business management.…”
Section: Introductionmentioning
confidence: 99%